2013
DOI: 10.5665/sleep.2878
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Noninvasive Positive Pressure Ventilation (NPPV) Versus Servoventilation in Patients with CPAP-Induced Central Sleep Apnea (Complex Sleep Apnea)

Abstract: After 6 weeks, servoventilation treated respiratory events more effectively than NPPV in patients with complex sleep apnea syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…The study showed that both ASV and BPAP effectively resolve treatment-emergent CSA during the titration night, but only ASV maintained an effective suppression of CSA over time. Thus, ASV appears superior to BPAP for the long-term treatment of persistent CSA.The most intriguing observation from Dellweg et al 10 was the re-emergence of central events after 6 weeks with BPAP, despite the apparent absence of events on the titration night. Ideally, BPAP should effectively eliminate all central events if there is an adequate backup rate, tightly sealed mask, sufficient pressure support (inspiratory driving pressure), and stable respiratory mechanics.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The study showed that both ASV and BPAP effectively resolve treatment-emergent CSA during the titration night, but only ASV maintained an effective suppression of CSA over time. Thus, ASV appears superior to BPAP for the long-term treatment of persistent CSA.The most intriguing observation from Dellweg et al 10 was the re-emergence of central events after 6 weeks with BPAP, despite the apparent absence of events on the titration night. Ideally, BPAP should effectively eliminate all central events if there is an adequate backup rate, tightly sealed mask, sufficient pressure support (inspiratory driving pressure), and stable respiratory mechanics.…”
mentioning
confidence: 80%
“…The most intriguing observation from Dellweg et al 10 was the re-emergence of central events after 6 weeks with BPAP, despite the apparent absence of events on the titration night. Ideally, BPAP should effectively eliminate all central events if there is an adequate backup rate, tightly sealed mask, sufficient pressure support (inspiratory driving pressure), and stable respiratory mechanics.…”
mentioning
confidence: 96%
“…Bi-level positive airway pressure (BPAP) can be considered to treat patients with CompSAS; however, there has been some association with worsening central apneas [58]. A randomized controlled trial comparing BPAP and ASV showed that after 6 weeks, ASV was clearly superior with regards to residual AHI and elimination of central events [59]. Currently available evidence suggests that ASV is effective at treating treatment-emergent central sleep apnea.…”
Section: Asv For Treatment-emergent Central Sleep Apneamentioning
confidence: 99%
“…Although the scientific evidence for several of these situations is limited, data from cohort studies, follow-up series and some randomized controlled trials demonstrated the efficacy of ASV and its superiority to other treatment options, including oxygen, CPAP, bilevel PAP in spontaneous timed mode (BPAP-ST) [25,56,82,83]. Teschler et al applied different therapeutical options (O 2 , CPAP, BPAP-ST, ASV) randomly for one night each.…”
Section: Adaptive Servoventilationmentioning
confidence: 99%